The concept of the Buddha : its evolution from early Buddhism to the trikāya theory - Guang, Xing, 1962- (RoutledgeCurzon critical studies in Buddhism., 2005)
This book presents an analysis of one of the fundamental Mahayana Buddhist teachings, namely the three bodies of the Buddha (the Trikaya Theory), which is considered the foundation of Mahayana philosophy.